2019
DOI: 10.1088/2631-8695/ab561c
|View full text |Cite
|
Sign up to set email alerts
|

Application of Taguchi design method for optimization of spark plasma sintering process parameters for Ti-6Al-4V/ h -BN binary composite

Abstract: Taguchi design method of optimization facilitates standard experimental research, lowers cost, conserves energy and time, minimizes waste and ensures optimal outcomes. In this work, Taguchi L9 3 4 orthogonal array, signal-to-noise (S/N) ratio and analysis of variance (ANOVA) statistical procedures were applied to evaluate the influence of sintering parameters/levels on the relative densification and microhardness of Ti-6Al-4V/h -BN binary composite sintered. The S/N ratios revealed that heating rate with delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The results showed also that for deformation there was a statistical evidence that Cutting speed and intensity had a significant effect on the response as the p-values obtained were less than 0.05, 24 the values obtained were successively 0.031 and 0.026 but there was no evidence that pressure had a significant effect as the pvalue was 0.235. In the other hand, the results showed that there was no statistical evidence that the effects were significant for the heat affected zones.…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 86%
“…The results showed also that for deformation there was a statistical evidence that Cutting speed and intensity had a significant effect on the response as the p-values obtained were less than 0.05, 24 the values obtained were successively 0.031 and 0.026 but there was no evidence that pressure had a significant effect as the pvalue was 0.235. In the other hand, the results showed that there was no statistical evidence that the effects were significant for the heat affected zones.…”
Section: Analysis Of Variance (Anova)mentioning
confidence: 86%
“…The signi cantly reduced wear rates of the optimized samples, in contrast to the matrix as presented in Figure 9 (a-c), seemed to be as a result of the achievement of re ned grains, better pore lling and formation of solid matrix-reinforcement interfacial integrity producing increased hardness of the material. This remarkable development is typical of SPS operation promoted by the high temperature of sintering and low heating rate during the experiment [26,38]. Moreover, increased wear rate can be facilitated by large plastic deformation of the ductile matrix, whereas incorporating a harder reinforcing phase (h-BN) in the ductile matrix to some degree can lessen its ductility thereby reducing the propensity to wear easily [46,49].…”
Section: Densi Cation and Mechanical Behaviour Studiesmentioning
confidence: 92%
“…Calculation according to the rule of mixture was used to obtain the theoretical density and the experimental density was obtained by taking the average of six repeated measurements for each sample. Next, the densi cation of each sample was calculated by dividing the experimental density by the theoretical density and multiplied by 100% while the porosity was calculated by removing the densi cation value from 100% [37][38].…”
Section: Methodsmentioning
confidence: 99%
“…This method has been previously used in optimization of processing parameters of both metal and polymer matrix composites and was reported effective for such purpose. 22,[29][30][31][32] The Taguchi optimization method uses factors and levels in design of experiment in orthogonal array. 29 The outcomes or responses of the designed experiment can be numerically modelled to determine the interactions and effects of factors on the parameters under investigation.…”
Section: Introductionmentioning
confidence: 99%